Health utility of children with acute lymphoblastic leukemia in China - Wang, Wei; Dong, Yaqi; Ji, Mingjing; Zhang, Xiaoyan; Cai, Jiaoyang (Frontiers in Public Health, 2023)
Background: Acute lymphoblastic leukemia is the most common cancer in children. As the 5-year survival rate has been improved to over 80%, more emphasis is now placed on reducing therapy toxicities and enhancing health-related quality of life (HRQoL) of patients during treatment. Our objective was to measure health utility of pediatric acute lymphoblastic leukemia (pALL) patients in China, examine utility weights of different treatment phases and influencing factors of health utility, as well as identify which aspects of HRQoL were most impaired. Methods: A cross-sectional study was conducted in Shanghai Children’s Medical Center (SCMC) Affiliated to Shanghai Jiao Tong University School of Medicine in China from April to November 2021. Primary caregivers of 247 patients completed the assessment by CHU9D-CHN and health utility scores were computed for all the patients and stratified by treatment phrases. Various multivariable models were constructed and the best was chosen to identify independent factors associated with utility scores. Factors affecting the most impaired dimensions were also examined. Results: The overall mean (SD) health utility score was 0.79 (± 0.174) and significantly increased from induction (0.73 [± 0.19], P<0.001) to consolidation (0.74 [± 0.18]), and to maintenance (0.82 [±0.16]). After adjusting for potentially influencing factors, utility scores in induction (Beta =-0.086, P =0.005) and consolidation (Beta =-0.074, P =0.043) were constantly lower than those during maintenance. In item-level analysis, lower age and induction phase were found to be significantly associated with high severity reported on the “school work/homework” dimension. Additionally, only the induction phase (vs. maintenance, OR=2.24, P = 0.016) was independently associated with the high severity level reported on the “able to join in activities” dimension. Conclusions: This is the first study that measured health utility of children with pALL in China. Mean health utility scores increased from induction to maintenance. These provided important utility estimates that help inform future health economic models. The phrasing of “School work/homework” in CHU9D-CHN could be further improved. More efforts are needed to design and implement specific interventions targeting at the dimension “able to join in activities” for enhancing HRQoL of children with pALL in China.